Exploring the restoration of Zostera capensis in Langebaan Lagoon: ecological, molecular and physiological perspectives - Watson, Katie Margaret (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.